Antibiotic Modulation of Capsular Exopolysaccharide in Pelagicoccus enzymogenes sp. nov. Isolated From Marine Sediment - Feng, Xi; Gong, Ya; Ye, Meng-Qi; Du, Zong-Jun (Frontiers in Marine Science, 2021)
Although Verrucomicrobia is widely distributed in the marine environment, their physiological or cellular properties are poorly characterized because of the lack of cultured representatives. Under the selective pressure of two antibiotics, ofloxacin and norfloxacin, a Gram-stain-negative, aerobic coccus with exopolysaccharide (EPS) production ability was isolated from the coastal sediment of Xiaoshi Island, Weihai, PR China. These antibiotics inhibited bacterial growth, giving rise to the relatively slow-growing Verrucomicrobia that formed colonies on the isolation plates. It may be an effective method for the isolation of Puniceicoccaceae. From the taxonomic data obtained in this study, the new marine isolate NFK12T (=KCTC 72940T=MCCC 1H00424T) is proposed to be placed into a novel species within the genus Pelagicoccus for which the name Pelagicoccus enzymogenes sp. nov. is proposed. The EPS production of the strain NFK12T and the related strains were investigated and the effect of EPS produced by the strain NFK12T on the growth of other strains was examined. Besides, the effect of EPS on tolerance to ofloxacin and norfloxacin of the strain NFK12T was studied by measuring the biomass of the strain NFK12T. It was deduced that those strains that produced EPS tentatively protected themselves against the inhibitory effects of ofloxacin and norfloxacin.